Recombinant FSH Improves Sperm DNA Damage in Male Infertility: A Phase II Clinical Trial - Colacurci, Nicola; De Leo, Vincenzo; Ruvolo, Giovanni; Piomboni, Paola; Caprio, Francesca; Pivonello, Rosario; Papaleo, Enrico; La Verde, Eugenio; Depalo, Raffaella; Lispi, Monica; Longobardi, Salvatore; Paoli, Donatella; et al. (Frontiers in Endocrinology, 2018)
ABSTRACT Background and objectives: Male infertility is a global health dilemma and Follicle-Stimulating Hormone (FSH) administration has shown promising results. Several studies showed that infertile men with normal semen parameters have low levels of DNA damage while infertile men with abnormal semen parameters have more damage at the DNA level. Sperm DNA damage may affect the reproductive outcome and has been associated with failure in the achievement of competent embryos and pregnancy fulfilment. The aim of this study was to evaluate whether the administration of recombinant FSH (Gonal-f ® PEN 900 IU) could improve sperm DNA fragmentation in men with infertility. The secondary endpoints of this study were to evaluate the FSH effects on sperm parameters and hormonal assets. Methods: A longitudinal, prospective, multicenter, open-label clinical trial was carried out. Infertile couples were recruited from six Italian Reproductive Medical Centers and 115 infertile men were enrolled for this study. All participants were treated with subcutaneous injections of Gonal-f® 150 IU every other day, within a three month-time frame. The semen samples were examined in accordance to the 2010 World Health Organization criteria. Sperm DNA Fragmentation (DFI) was determined by fluorescence microscopy using terminal deoxynucleotidyl transferase-mediated d-UTP Nick-end Labelling (TUNEL) assay. Statistical analysis was performed using both the t-test for paired samples and the Wilcoxon signed-rank test. Results: FSH administration improved DFI in 67% of patients, with an average decrease of 35.4% compared to the baseline. This improvement is more evident in men with basal DFI lower than 17% and in those with FSH basal levels between 2.16 and 4.27 IU/L. In addition, FSH enhanced the gonadal function, increasing the hormones AMH and Inhibin B and semen parameters. Limitation of these results are represented by the absence of a placebo group and of FSHR genotype stratification sub-analysis. Conclusion: Recombinant FSH 150 IU is well tolerated and effective in eliciting a significant DFI reduction as well as in improving gonadal function. Trial Registration: EUDRACT Number 2010-020196-23. Registred 14 April 2011